PENGARUH PARTISIPASI ANGGARAN, KEJELASAN SASARAN ANGGARAN, DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL - Sausan Syifa Qotrunnada; Adi Wiratno; Saras Supeno (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2018)
This study aims to examine the effect of budgetary participation, budget target clarity and organizational commitment on managerial performance empirical study in PD BPR BKK Purwokerto. To collect data of this study, survey questionnaire with sample selection using purposive sampling method are used. Questionnaires given to 33 managers or managers-equaled level in PD BPR BKK Purwokerto. Their responses are analyzed using multiple linear regression analysis technique through SPSS software. These analysis results reveal that budgetary participation and budget target clarity has significant positive effects to managerial performance. However, organizational commitment does not affect to managerial performance. Keywords: Budgetary Participation, Budget Target Clarity, Organizational Commitment, Managerial Performance.